If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 + -2x = 11 Reorder the terms: 2 + 5x + -2x = 11 Combine like terms: 5x + -2x = 3x 2 + 3x = 11 Solving 2 + 3x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 11 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 11 + -2 3x = 11 + -2 Combine like terms: 11 + -2 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 2m^2-6m-24=0 | | 3(2a-4/b^2) | | x+10=-3x+14 | | 5x^2-16-x^2/2 | | sin(1.5x)=(3x) | | (x-3)(x+4)=18 | | (x-3)(x+4)=-18 | | (-1/4)^(1/3) | | -27x=-7 | | (3x+4)(3x+4)=0 | | 5u/4=20 | | 18z=72 | | 2w+8x-13y+6w+5x+8y= | | -3x-3(2x+6)=-117 | | 12=6/5y | | X^2-18x=-65 | | e^1-5x=793 | | A=3x-2y+7+y-5x | | 4x-5(-4+18)=102 | | 3x-2y+7+y-5x= | | 5a-6ifA=4 | | 4(3)+4(x)=28 | | -3x-6+2-x= | | 6x+44=80 | | y=-4/9x | | (4-7i)/(-6-5i) | | 43-4x=13-7x | | 10-4x=42 | | 7+1.5x-17-5.5x= | | -3x^2+12x=15 | | 3ln(x-3)=6 | | 81^(3/2)=x |